METHOD AND SYSTEM FOR 2D-3D IMAGE REGISTRATION (2013)
A method of 2D-3D image registration is presented. The method includes accessing a two dimensional image of a subject having an object therein, accessing a three dimensional image data of the subject with the object f, generating a plurality of mesh models from the three dimensional image data, wherein the plurality of mesh models comprise a first mesh model having a first attenuation coefficient and a second mesh model having a second attenuation coefficient, rendering the first mesh model and the second mesh model with a projection geometry of the two dimensional image to obtain a resultant image, iteratively comparing the resultant image with the two dimensional image using a similarity measure, and registering the two dimensional image with the resultant image.